Pengembangan Prototipe Model Sistem Tata Kelola Dan Pengawasan Proses Akademik Pada Universitas Atma Jaya Makassar - Syarif, Adi Chandra; Gunawan, Farid Hartono; Lisangan, Erick Alfons (TEMATIKA, Journal of Informatics and Information Systems, 2015)
With the issuance of PP No. 19 In 2005, Internal Quality Assurance System (SPMI) has become an necessity for an higher education institution that aims to achieve continuous improvement. Most colleges including Universitas Atma Jaya Makassar has implemented a model of management and control system for academic process by relying on the outcome of process, not the concurrent of the process itself. In order to achieve continuous improvement, the quality assurance system needs a control system that not only rely on the outcome but more important is the implementation the process itself. This research aims to develop a prototype model of management and control system of academic process that focuses on the monitoring and evaluating function of the academic process, especially the academic process which runs at theUniversity of Atma Jaya Makassar. This research uses UML methodology based on objectoriented approach to take advantage on computer networks as the supporting technology. The prototype model of the resulting system will help facilitate the implementation and quality assurance of academic process through increased control and evaluation function in a structured academic process and in real timeKeywords: supervision, governance, higher education, prototype, model, system